Ἡ γυναικεία ἐκπαίδευση καὶ ὁ γλωσσικὸς ἐξελληνισμὸς τῶν τουρκόφωνων Ρωμιῶν τῆς Μικρᾶς Ἀσίας: Tὸ Ὁμήρειο Παρθεναγωγεῖο Σμύρνης (1881-1922) - Καμούζης, Δημήτρης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
The purpose of this article is to highlight the role and the importance of women’s education in relation to the acculturating efforts of the educated and wealthy Greek Orthodox elites aiming at the linguistic Hellenization of the Turkish-speaking Greek Orthodox population of the Ottoman Empire. Taking as a case study the Homereion Girls’ School [Ομήρειον Παρθεναγωγείον Σμύρνης] founded in Smyrna in 1881, the paper examines the educational activities of the school both in Smyrna and inner Anatolia from the late 19th century until the collapse of the Asia Minor front and the burning of Smyrna in 1922. The importance the school’s founders and board attributed to Greek education and culture as an integral part of a student-focused Hellenic consciousness cultivating process, the preparation of female teachers who were entrusted with the mission to teach the Greek language to the Turkish-speaking Rum children in the interior of Anatolia and finally the close and continuous collaboration of the Homereion School with the Greek state are some of the basic issues this paper will attempt to elucidate in an effort to assess whether and to what extent this educational policy was successful. The research draws on material from the Diplomatic and Historical Archives of the Greek Ministry of Foreign Affairs, the archives of the “Association of Asia Minor Greeks ‘Anatoli’ ”, the Lampakis Family Archives and secondary bibliography.